New Readings in Arabic Historiography from Late Medieval Egypt and Syria : Proceedings of the themed day of the Fifth Conference of the School of Mamluk Studies - Steenbergen, Jo van,; Termonia, Maya, (Islamic History and Civilization ;, 2021)
New Readings in Arabic Historiography contributes to research on Arabic texts of history from late medieval Egypt and Syria. Departing from dominant understandings of these texts through the prisms of authenticity and "literarization," it engages with questions of textual constructedness and authorial agency. This edited volume consists of 13 contributions by a new generation of scholars. Each of the volume's three parts represents a different aspect of their new readings of particular texts. Part one looks at concrete instances of textual interdependencies, part two at the creativity of authorial agencies, and part three at the relationship between texts and social practice. New Readings thus participates in the revaluation of late medieval Arabic historiography as a critical field of inquiry.